PENGARUH DISIPLIN, BALAS JASA DAN KETELADANAN PIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI DINAS KESEHATAN KABUPATEN SUKOHARJO - Riyaniningsih, Sumbar Prih; Triyaningsih, SL - (Universitas Slamet Riyadi, 2010)
ABSTRACT The purpose of this study was to analyze the effect of variable significance discipline, remuneration, and exemplary leadership on employee motivation Sukoharjo District Health Office. The population in this study were all Civil Servants Health Department Sukoharjo totaling 100 people. Study sample totaled 50 people taken from populsi by simple random sampling technique. Baseline data were collected by questionnaire and documentation techniques. The data obtained were processed by multiple linear regression techniques. The results of the analysis stated discipline variables do not significantly influence employee motivation, variable remuneration significant effect on employee motivation and exemplary leadership variables significantly influence employee motivation Sukoharjo District Health Office. Assay coefficient of determination R2 = 0,467, which means the amount of donations variable discipline, remuneration and exemplary leadership on employee motivation District Health Sukoharjo of 46,7%. Keywords: discipline, remuneration, exemplary leadership and motivation.